(untitled) (Semiárida, 2020)
Effects of plains vizcachas on the species richness of plants in the semiarid scrub were studied in Uhue Calel National Park, Argentina, from May to December 1993. Vizcachas are colonial, herbivorous rodents, that live in communal burrows systems (vizcacheras), which are occupied for many generations. Each social group of vizcachas forages in an exclusive home range around the burrows. Species richness was measured at 4 active vizcacheras along belt transects (20 m x 90 m long) extending ou1ward from the burrow system into the ungrazed matrix. Total species richness increased with distance from the burrows and reached a plateau in the ungrazed matrix rather than at moderate levels of grazing as predicted from the intermediate disturbance hypothesis. This pattern was more similar to pattems predicted by a grazing model that considers evolutionary history and environment moisture.